2008
DOI: 10.1007/s00264-008-0517-z
|View full text |Cite
|
Sign up to set email alerts
|

A new technique for lag screw placement in the dynamic hip screw fixation of intertrochanteric fractures: decreasing radiation time dramatically

Abstract: The goal of this study was to confirm the decrease in radiation time required for a new technique to place dynamic hip screws (DHS) in intertrochanteric fractures. Seventy-six patients were treated with DHS by either the new technique (NT) or the conventional technique (CT). The width of femoral shaft, the length of the hip screw to be implanted into the injured side, and the distance between the tip of the greater trochanter and the entry point of the guide wire were measured at the uninjured side on the ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Several methods have been described for accurate guidewire placement in fixation. [14][15][16][17][18][19][20][21][22] Some authors locate the entry point approximately 2 cm below the vastus lateralis ridge; however, this method is not reproducible without a reliable osseous landmark. Adams and Stossel 14 used staples as groin skin markers to guide the placement of the guidewire, and Aronson and Carlson 15 used a marker pen instead of staples in the treatment of slipped capital femoral epiphysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several methods have been described for accurate guidewire placement in fixation. [14][15][16][17][18][19][20][21][22] Some authors locate the entry point approximately 2 cm below the vastus lateralis ridge; however, this method is not reproducible without a reliable osseous landmark. Adams and Stossel 14 used staples as groin skin markers to guide the placement of the guidewire, and Aronson and Carlson 15 used a marker pen instead of staples in the treatment of slipped capital femoral epiphysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not clearly define a reference landmark on the AP plane, and the study showed no decreased radiation exposure. Sheng et al 22 proposed a geometric equation to calculate the entry point of a Kirschner wire, but the procedure required exposing the lesser trochanter to increased trauma and surgery time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2.5-16 % of cases, the hip screw may ultimately "cut out", i.e. penetrate the femoral head in its superior part [9][10][11][12][13][14][15]. Early detection of DHS® migration is important to reduce patient morbidity.…”
Section: Introductionmentioning
confidence: 99%